New specimens of Allodaposuchus precedens from France: intraspecific variability and the diversity of European Late Cretaceous eusuchians. (17th September 2015) - Martin, Jeremy E.; Delfino, Massimo; Garcia, Géraldine; Godefroit, Pascal; Berton, Stéphane; Valentin, Xavier
Abstract : A series of cranial remains as well as a few postcranial elements attributed to the basal eusuchian A llodaposuchus precedens are described from Velaux‐La Bastide Neuve, a Late Cretaceous continental locality in southern France. Four skulls of different size represent an ontogenetic series and permit an evaluation of the morphological variability in this species. On this basis, recent proposals that different species of A llodaposuchus inhabited the European archipelago are questioned and A . precedens is recognized from other Late Cretaceous deposits of France and Romania. A dentary bone is described for the first time in A . precedens and provides a basis to reconsider the validity of two taxa, I schyrochampsa meridionalis and M usturzabalsuchus buffetauti, which are interpreted as possible junior synonyms of A llodaposuchus . These results allow the diversity of Late Cretaceous eusuchians from Europe to be refined and recognize a basal stock known as the Hylaeochampsidae sharing an absence of external mandibular fenestrae. Within this family, A llodaposuchus occupies a basal position relative to A cynodon, I harkutosuchus and H ylaeochampsa . © 2015 The Linnean Society of London